Effects of kinetic- and kinematic-oriented change-of-direction training on anterior cruciate ligament risk factors in elite soccer players under fatigue - Altug, T.; Soyler, M.; Aydin, A. S.; Celik, S.; Taber, C. B. (The Journal of Strength and Conditioning Research, 2026)
This study investigated the effects of repeated change-of-direction (COD) drills on body composition and performance outcomes in elite U17 soccer players, examining fatigue-induced changes in anterior cruciate ligament (ACL) injury risk mechanisms. Twenty-eight male athletes (age: 16.8 ± 0.6 years; height: 167.4 ± 2.3 cm; body mass: 63.50 ± 2.19 kg; fat mass (FM): 5.31 ± 0.90 kg; fat-free mass (FFM): 58.20 ± 0.84 kg) were randomly assigned to either a kinetic group emphasizing resistance-based force production or a kinematic group targeting agility and COD mechanics. A 12-week in-season intervention was conducted, with pretest and posttest evaluations of heart rate (HR), blood lactate (LA), rating of perceived exertion (RPE), FM, FFM, COD time, and shuttle sprint (SS) performance. Significant group × time interactions were observed for FM (F (1, 26) = 6.07, p = 0.021, Eta2 = 0.189), SS (F (1, 26) = 5.75, p = 0.024, Eta2 = 0.181), and RPE (F (1, 26) = 13.52, p = 0.001, Eta2 = 0.342), favoring the kinetic group. These athletes exhibited greater reductions in FM, smaller increases in sprint time, and elevated RPE, indicating improved fatigue tolerance. No interaction effects were found for COD, HR, or LA, but the kinetic group exhibited more effective within-group adaptation to training-induced fatigue. Overall, kinetic-based COD training may support neuromuscular and metabolic adaptation under fatigue, while kinematic approaches may better preserve movement quality. A combined approach may mitigate fatigue-related ACL injury risk during competition.